Quality Improvement Needs for Vocational High School Teachers in Indonesia - Nurhadi, Didik (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Vocational high school quality is determined by the workability of its graduates, the partnerships with business and industry, as well as the professionalism of its teachers. The purpose of this study is to identify the needs of quality improvement of vocational high school teachers in accordance with the Teachers’Disposition Index focusing on student-centered dimension, professionalism, and curriculum‐centered dimension. The study employed a questionnaire survey as the methodology, and the sample of the population was randomly selected 300 teachers in Indonesia. The findings showed that teachers need to improve their quality in the aspect of student-centered dimensions, including effective instructional strategies, responsibility, learning environment, and collaboration with others. While, professionalism and curriculum-centered dimension, including teacher’s knowledge and positive attitude, facilitation of learning, communication skill, and implementation of the curriculum and learning programs. Based on the results, our expectation is that vocational high school teachers should improve teaching quality by developing student-centered learning environment and teachers’ professionalism to make students learn more optimally.